Individual Differences Modulate the Effects of tDCS on Reading in Children and Adolescents with Dyslexia. (2nd November 2021) - Lazzaro, Giulia; Costanzo, Floriana; Varuzza, Cristiana; Rossi, Serena; De Matteis, Maria Elena; Vicari, Stefano; Menghini, Deny
ABSTRACT: Emerging evidence suggests that the combination of transcranial direct current stimulation (tDCS) and reading training may provide promising benefits for dyslexia; however, the clinical effects and the role of individual differences in tDCS outcomes for dyslexia remain unclear. To this end, the present study investigated the effects of tDCS on clinically relevant reading measures and examined factors (i.e. reading at baseline, age, and intelligence quotient [IQ]) that may contribute to improvements following tDCS treatment. Our results showed that, in terms of word reading fluency, the percentage of responders in the active tDCS group was higher than that in the sham tDCS group. Linear mixed effects models showed that the effect of tDCS and reading training tasks on word reading fluency depended on reading at baseline with age and IQ. Thus, the present study provides research-based selection criteria for potential responders to tDCS and encourages tailored intervention based on individual characteristics.